Geo Bogza – lecţia de libertate şi poetica exasperării - Loredana Opăriuc (Revista de Istorie și Teorie Literară)
Geo Bogza is one of the well-known representatives of the Romanian avant-garde and one of the unavoidable names during the second half of the 20th century, covering different types of literary languages. His works contain, as a common feature, the idea of real freedom, not an imagined one, a poet, or a writer in general, being, in his view, necessarily free from society rules, literary conventions, prejudices and other restrictive laws. His articles, as well as his poems and prose, proclaim the literature which serves the human being, against not only traditional canons but also modern formalism. The craft of writing is no longer considered a heavenly gift, on the contrary is seen as the only way to escape from a tight reality in order to make it better, the obsessive metaphor of the “yellow maid” describing this larger and prolific poetic reality. That is why almost every lyric or line he wrote is an anathem to human and cosmic beauty, sometimes rhetoric and pathetic, but with authentic tunes.